Variabel-Variabel Yang Mempengaruhi Permintaan Dan Penawaran Mudharabah Pada Perbankan Syariah Di Indonesia: Variables that Affect Demand and Supply of Mudaraba at Shariah Banking in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Abstract: This thesis aims to estimate variables affecting demand and supply of mudaraba in Indonesia .Methodology that used is regression with single equation with ARCH and Iterative Cochrane Orcutt. Demands of mudaraba are affected by level of return (negative), expected profit (positive) while supply of mudaraba are affected by level of return (positive), funding (positive), and capital per asset (positive).